Imprisoning communities: how mass incarceration makes disadvantaged neighborhoods worse - Clear, Todd R. (Studies in crime and public policy, 2007)
A detailed and empirical exploration of the effects of mass incarceration in poor areas, 'Imprisoning Communities' demonstrates that, in high doses, incarceration contributes to the very social problems it is intended to solve.